SYNTHESIS AND CHARACTERIZATION OF MESOPOROUS TIO2 USING POLY-VINYLPYRROLIDONE (PVP) TEMPLATE AS ENZYMATIC ELECTROCHEMICAL SENSING MATERIAL FOR GLUCOSE DETECTION - Amri, Fauzan
Mesoporous TiO2 has been successfully synthesized using titanium tetraisopropoxide (TTIP) precursor and polyvinypyrrolidone (PVP) template via the hydrothermal method at a heating temperature of 170 °C for 10 h. PVP polymer play an important role in creating mesoporous structures in TiO2 because of its water-solubility and good biocompatibility properties. There are two samples produced in this study, namely mesoporous TiO2 synthesized with ethanol (TiO2 (E)) and mesoporous TiO2 synthesized with aquadest (TiO2 (A)). The two samples have pore sizes of 10.95 nm and 13.84 nm, respectively, with a surface area of 100.81 m2 g-1 for TiO2 (E) and 87.15 m2 g-1 for TiO2 (A). Ethanol solvent can effectively regulate the rate of condensation and hydrolysis so that it can increase the regularity of the pore structure and affect the surface area of TiO2. The phase and crystal structure identified in both TiO2 (E) and TiO2 (A) samples were anatase with a tetragonal structure and the resulting crystal sizes were 10.78 nm and 11.28 nm, respectively. Based on SEM and HRTEM analysis, the nanoparticles produced in TiO2 (E) and TiO2 (A) samples are spherical in shape and the pore structure formed comes from particle packing with agglomeration in some parts of the sample. The success of glucose oxidase (GOx) enzyme immobilization on mesoporous TiO2 surface is marked by the appearance of peaks of amide I and II spectra in the FTIR spectrum of TiO2(E)/GOx and TiO2 (A)/GOx and differences in UV light absorption in mesoporous pure TiO2 and TiO2/GOx samples. From the results of testing the performance of the biosensor using the electrochemical method on the GCE/TiO2(E)/GOx electrode, it was obtained a sensitivity value of 0.643 ?A mM-1 cm-2, a linear range from 0.1 to 2 mM, and a detection limit of 95 ?M.